GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 439 species occurrences available in GBIF matching the query: TaxonKey: Posidonia oceanica (L.) Delile Geometry: POLYGON((-9.492187 44.276671,-9.492187 35.889050,4.570312 35.889050,4.570312 44.276671,-9.492187 44.276671)) HasCoordinate: true Year: >= 1975. The dataset includes 439 records from 18 constituent datasets: 1 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 1 records from Australia's Virtual Herbarium. 2 records from iNaturalist Research-grade Observations. 2 records from Diveboard - Scuba diving citizen science observations. 26 records from naturgucker. 1 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1 records from Natural History Museum, Vienna - Herbarium W. 2 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 2 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Herbario de la Universidad de Almeria. 384 records from Posidonia Oceanica Survey 2005 (EurOBIS). 5 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 3 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 1 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 4 records from Herbario de Universidad de Murcia: MUB. 1 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Carnet en Ligne. 1 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA.
Keywords: GBIF; biodiversity; species occurrences